2008
DOI: 10.1186/1743-8977-5-13
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to ambient concentrations of particulate air pollution does not influence vascular function or inflammatory pathways in young healthy individuals

Abstract: Background: Particulate air pollution is associated with increased risk of cardiovascular events although the involved mechanisms are poorly understood. The objective of the present study was to investigate the effects of controlled exposure to ambient air fine and ultrafine particles on microvascular function and biomarkers related to inflammation, haemostasis and lipid and protein oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
75
2
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 59 publications
(89 reference statements)
9
75
2
3
Order By: Relevance
“…However, in a related study, no statistically significant differences were observed in young, healthy subjects. 27 These results, along with the previously reported results by Bräuner and colleagues 26 suggest that cumulative exposure of 2 or more days to ambient PM 2.5 pollution may adversely affect vascular function. However, these results provide no evidence of a contemporaneous vascular response to a few hours of controlled exposure.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…However, in a related study, no statistically significant differences were observed in young, healthy subjects. 27 These results, along with the previously reported results by Bräuner and colleagues 26 suggest that cumulative exposure of 2 or more days to ambient PM 2.5 pollution may adversely affect vascular function. However, these results provide no evidence of a contemporaneous vascular response to a few hours of controlled exposure.…”
Section: Discussionsupporting
confidence: 68%
“…[23][24][25] Recently, and before the completion of this study, Bräuner and colleagues reported the results of two studies of vascular function that were also based on RH-PAT measures. 26,27 They reported that reductions in 48-hr PM 2.5 due to filtering air in subjects' homes resulted in improved vascular function in aged subjects. 26 However, they found no relationship between traffic-related particles and vascular function in young healthy individuals.…”
Section: Technical Papermentioning
confidence: 99%
See 1 more Smart Citation
“…Um estudo cruzado com 29 participantes que se exercitaram ou não na bicicleta e estiveram expostos a poluentes do ar não encontrou qualquer associação significativa dos poluentes atmosféricos com a contagem de hemoglobina, GV e plaquetas e com marcadores de inflamação em jovens adultos saudáveis 30 . As associações entre poluentes do ar e parâmetros hematológicos em nosso estudo são consistentes com os efeitos crônicos dos poluentes atmosféricos sobre os fatores hematológicos em adultos 16 ; portanto, nossos achados podem ser decorrentes da exposição crônica das crianças estudadas aos poluentes do ar, ou da maior susceptibilidade das crianças ao risco dos poluentes atmosféricos para a saúde.…”
Section: Discussionunclassified
“…Inthat study young healthy volunteers exercising on bicycle ergometers were exposed to diesel exhaust derived from engine condition mimicking vehicles functioning in urban environment, with acceleration retardation and variation in engine load as well as periods of constant speed and idling [Barath et al, 2010]. Conversely a similar study found no changes in micro-vascular vasodilation, blood coagulation parameters or markers of systemic inflammation related to particle exposure in healthy volunteers exercising on an ergometer bicycle and breathing air from one of Copenhagen's busiest roads [Brauner et al, 2008]. A study explored the possibility of reducing the cardiovascular effects of short-term air pollution exposure to urban pollution by wearing a simple facemask.…”
Section: Short-term Exposure To Air Pollutants Effects On the Cardiovmentioning
confidence: 95%